Positive association of neck circumference and cardio-metabolic risk factors in Ekiti, Nigeria - Raimi, Taiwo Hussean; Dada, Samuel Ayokunle; Solanke, Abimbola (Journal of Surgery and Medicine, 2018)
Aim: The association between neck circumference (NC) and cardiometabolic risk factors in Southwest Nigeria is unknown. The study aimed at determining the relationship between NC and cardiometabolic risk factors. Methods: Result of a cross-sectional health survey involving residents of Ado-Ekiti/Ika community in Ekiti State was analyzed. Clinical measurements of body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), neck circumference, systolic/diastolic blood pressures (SBP & DBP) were taken, and random blood glucose (RBG) determined. Bivariate correlations and linear regression models were computed for each sex. Results: There were 211 participants out of which 78 (37.0%) were men. Among men, NC was significantly correlated with weight (r=0.412, p<0.001) and BMI (r=0.362, p<0.01). Among women, NC correlated with weight (r=0.319, p<0.001), BMI (r=0.228, p<0.01), WC (r=0.238, p<0.01), SBP (r=0.444, p<0.001), DBP (r=0.423, p<0.05), and RBG (r=0.203, p<0.05). NC independently predicted SBP, ORs (95%CI), 2.707 (1.468-3.946) and DBP, ORs (95%CI), 1.780 (0.950-2.611) in women, but not in men. While only the NC of men with general obesity was greater than those who do not have, 39.27(5.68)cm vs 36.96(3.46)cm, p=0.04, the NC of women who were obese or had hypertension were significantly greater than those who were not: general obesity, 33.17(2.58)cm vs 31.57(3.08cm), p=0.002; central obesity, 32.88(2.99)cm vs 31.09(2.62)cm, p<0.001; hypertension, 34.39(2.77)cm vs 31.88(2.88)cm, p=0.001). Compared with those in the upper tertile, men with NC in the middle tertile had lower mean weight [60.82 (8.67) kg vs 68.90 (10.08) kg, p=0.005], BMI [21.31 (2.54) kgm2 vs 23.72 (3.77) kgm2, p=0.022], WC [78.32 (5.57) cm vs 85.14 (8.72), p=0.003], and WHtR [0.464 (0.06) vs 0.50 (0.06), p=0.004].Compared with those in the upper tertile, women with NC in the lower tertile had lower mean weight [56.81(9.80) kg vs 66.08(13.50)kg, p=0.031], SBP [107.53 (15.59) mmHg vs 132.38 (15.85) mmHg, p<0.001], and DBP [69.27 (10.91) mmHg vs 84.69 (10.52) mmHg, p<0.001]. Conclusions: Neck circumference has positive association with, and predicts cardiometabolic risk factors, and may serve as an index of obesity in Ekiti, Nigeria.